2012
DOI: 10.1111/nph.12069
|View full text |Cite
|
Sign up to set email alerts
|

Male‐specific DNA markers provide genetic evidence of an XY chromosome system, a recombination arrest and allow the tracing of paternal lineages in date palm

Abstract: SummaryWhether sex chromosomes are differentiated is an important aspect of our knowledge of dioecious plants, such as date palm (Phoenix dactylifera). In this crop plant, the female individuals produce dates, and are thus the more valuable sex. However, there is no way to identify the sex of date palm plants before reproductive age, and the sex-determining mechanism is still unclear.To identify sex-linked microsatellite markers, we surveyed a set of 52 male and 55 female genotypes representing the geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 38 publications
12
89
2
Order By: Relevance
“…Similarly, 3 female specific markers were identified in date palm by Younis et al (2008). Male specific alleles were identified by Cherif et al (2012) in 52 male genotypes of date palm using microsatellite markers. They found three genetically linked loci which were heterozygous only in males.…”
Section: Rapd Banding Patterns and Dendrogram Analysis Of Germplasmmentioning
confidence: 99%
“…Similarly, 3 female specific markers were identified in date palm by Younis et al (2008). Male specific alleles were identified by Cherif et al (2012) in 52 male genotypes of date palm using microsatellite markers. They found three genetically linked loci which were heterozygous only in males.…”
Section: Rapd Banding Patterns and Dendrogram Analysis Of Germplasmmentioning
confidence: 99%
“…The oases agroecosystems, perfectly adapted to the specific constraints of the environment, is largely shaped by the genetic diversity of the date palm. Cherif et al (2013) reported on male-and female-specific DNA markers and presented secondary statistics including number of alleles (A), H o , H e and F is (Table 4). Significant differences were found between FA (0.468) and MS (1.00) for Ho and between MS (-0.304) and each of MA (-0.012), and FA (-0007) for F is .…”
Section: Heterozygositymentioning
confidence: 99%
“…The difference between the magnitude of the r-values between Ne and each of Fis and PPL is worth further exploration in date palm. The observed heterozygosity estimates reported by Cherif et al (2013) on male-and female-specific DNA markers included secondary statistics on the fixation index of all four combinations of male and female autosomal and sex chromosomes. The relationships based on these four combinations were used to estimate Fis as a function of Ho, and plot the distribution of the four loci combinations (Figure 7).…”
Section: Fixation Indexmentioning
confidence: 99%
“…They identified two SCoT and four RAPD sex-specific markers. While, [12] employed the microsatellites marker system for the first time to identify three male-specific SSR markers tested on date palm genotypes collected from different geographic origin (Tunisia, Morocco, Italy, Djibouti, Oman, Syria and Iraq) with clearly ignoring for Egyptian genotypes (which produce about 20% of global dates). While, [11] identified male-linked markers, but this markers still requires confirmation, as the markers were validated only in a small sample and with an unsatisfactory accuracy of 90% [12].…”
Section: Previous Identification Of Sex-linked Markers In Date Palmmentioning
confidence: 99%
“…This studies included the uses of isozymes [7], peroxydases [8], molecular marker tool such random amplified polymorphic DNA (RAPD) [9,10], PCR-based restriction fragment length polymorphism (PCR-RFLP) approach [11], microsatellites [12], and recently; PCR-based approaches (RAPD and SCoT) [13].…”
Section: Introductionmentioning
confidence: 99%